Current Guideline of Chest Compression Depth for Children of All Ages May Be Too Deep for Younger Children - Jang Hee Lee; Sang Kuk Han; Ji Ung Na (Emergency Medicine International)
Aim. To determine whether the chest compression depth of at least 1/3 of the Anteroposterior (AP) diameter of the chest and about 5 cm is appropriate for children of all age groups via chest computed tomography. Methods. The AP diameter of the chest, anterior chest wall diameter, and compressible diameter (Cd) were measured at the lower half of the sternum for patients aged 1-18 years using chest computed tomography. The mean ratio of 5 cm compression to the Cd of adult patients was used as the lower limit, and the mean ratio of 6 cm compression to the Cd of adult patients was used as the upper limit. Also, the depth of chest compression resulting in a residual depth <1 cm was considered to cause internal injury potentially. With the upper and lower limits, the compression ratios to the Cd were compared when compressions were performed at a depth of 1/3 the AP diameter of the chest and 5 cm for patients aged 1-18 years. Results. Among children aged 1-7 years, compressing 5 cm was deeper than 1/3 the AP diameter. Also, among children aged 1-5 years, 5 cm did not leave a residual depth of 1 cm, potentially causing intrathoracic injury. Conclusion. Current pediatric resuscitation guidelines of chest compression depth for children were too deep for younger children aged 1-7 years.